(untitled) (Journal of Atomic and Molecular Sciences, 2019)
A balance between the local excitation (LE) and charge-transfer (CT) transitions is an important issue of a density functional. In this work, we compare the performance between the global hybrid functional M062X and long-range separated functional CAM-B3LYP when they calculate the absorption energies of visible light photoswitches hemithioindigo (HTI) Z1, Z2, Z4, Z5 and Z7. The electronic excitations of HTI Z1 and Z2 are mixtures of LE and CT transitions. CAM-B3LYP succeeds to predict the same absorption energy sequence of the five compounds as the experimental results while M062X predicts a wrong sequence of HTI Z1 and Z2. Another global hybrid functional M06 is also employed for a comparison. Finally, we suggest CAM-B3LYP rather than M062X when dealing with mixed electronic transtions.